A deep dive into cation-modified structural, mechanical, magneto‑electronic, and thermophysical properties of MAlO3 (M = Ca, Sr, Ba, and Ra): First-principles investigation - Asif Hosen; Md. Rafiqul Islam; Ahmad A. Mousa; Mohammed S. Abu-Jafar (Results in Engineering)
This article presents a first-principles investigation of structural, mechanical, thermophysical, and magneto-electronic properties of MAlO3 (M = Ca, Sr, Ba, and Ra) perovskites, which have not yet been synthesized experimentally. The ground state energies derived from structural optimizations imply that SrAlO3, BaAlO3, and RaAlO3 have stable ferromagnetic phases as opposed to non-magnetic phases like CaAlO3. The structural stability of the perovskite candidates under investigation is confirmed by the combined assessment of the tolerance factor and enthalpy of formation energy. Since no soft modes or imaginary frequencies are seen, the phonon dispersion spectra ensure the dynamic stability of the compounds with and without external stress. The spin-polarized electronic properties are calculated using Generalized Gradient Approximation (GGA) and Trans-Blaha modified Becke-Johnson (TB-mBJ) approaches. The electronic and magnetic characteristics of CaAlO3 reveal metallic features for both up-spin and down-spin channels. In contrast, SrAlO3, BaAlO3, and RaAlO3 have half-metallic characteristics displaying a metallic nature in the down-spin channel while acting as insulators in the up-spin channel. However, half-metallic properties are preserved within -6 % to +8 % of the applied strain for the compounds SrAlO3, BaAlO3, and RaAlO3. Under compressive stress, CaAlO3 retains its metallic characteristics; however, when tensile strain is above 4 %, the material loses these characteristics and becomes half-metallic. The mechanical characteristics demonstrate the ductility of the perovskites. Lastly, theoretical simulations of the thermodynamic and thermoelectric properties are included in this research. We may conclude that the calculated parameters of these half-metallic candidates pave the way for potential use in spintronic and thermoelectric devices.